2008
DOI: 10.2355/isijinternational.48.240
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fixed-bed Column for Cr(VI) Removal from Aqueous Solution Using Schwertmannite

Abstract: The fine particles of schwertmannite as an iron oxyhydroxide adsorbent has been suggested as a novel and strong Cr(VI) sorbent for treatment of Cr-contaminated industrial wastewater. The removal process was conducted in both batch and continuous trials. As a result of the batch experiments, the maximal adsorption capacity of the schwertmannite was obtained as 178 mg/g which was quite high amount in comparison with the usual applied Cr(VI) sorbents in the literatures. The continuous removal process involved a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
5
2
Order By: Relevance
“…The piercing points at pH 2 (initial conditions) and 4 were at approximately 50 and 90 min, respectively; however, it took approximately 100 min for the piercing point to appear at pH 8, earlier than that observed at pH 6. This increase in Cr(VI) removal over the pH span 2-6 was inconsistent with the results reported by Eskandarpour et al (2008) and Antelo et al (2012); however, it was confirmed by Chen and Zhou (2006), who reported that the maximum saturated adsorption amounts of Cr(VI) by schwertmannite in batch trials were obtained in the pH et al, 2011), and 7.0 (Antelo et al, 2012). The schwertmannite used in this study was obtained by a biological process, whereas studies by Eskandarpour et al (2008) and Antelo et al (2012) employed schwertmannite prepared by chemical processes.…”
Section: Effect Of Ph Valuescontrasting
confidence: 99%
See 2 more Smart Citations
“…The piercing points at pH 2 (initial conditions) and 4 were at approximately 50 and 90 min, respectively; however, it took approximately 100 min for the piercing point to appear at pH 8, earlier than that observed at pH 6. This increase in Cr(VI) removal over the pH span 2-6 was inconsistent with the results reported by Eskandarpour et al (2008) and Antelo et al (2012); however, it was confirmed by Chen and Zhou (2006), who reported that the maximum saturated adsorption amounts of Cr(VI) by schwertmannite in batch trials were obtained in the pH et al, 2011), and 7.0 (Antelo et al, 2012). The schwertmannite used in this study was obtained by a biological process, whereas studies by Eskandarpour et al (2008) and Antelo et al (2012) employed schwertmannite prepared by chemical processes.…”
Section: Effect Of Ph Valuescontrasting
confidence: 99%
“…This increase in Cr(VI) removal over the pH span 2-6 was inconsistent with the results reported by Eskandarpour et al (2008) and Antelo et al (2012); however, it was confirmed by Chen and Zhou (2006), who reported that the maximum saturated adsorption amounts of Cr(VI) by schwertmannite in batch trials were obtained in the pH et al, 2011), and 7.0 (Antelo et al, 2012). The schwertmannite used in this study was obtained by a biological process, whereas studies by Eskandarpour et al (2008) and Antelo et al (2012) employed schwertmannite prepared by chemical processes. Based on the fact that the maximum adsorption capacity of Cr(VI) was obtained at pH 6 (i.e., the schwertmannite surface is negatively charged), it can be concluded that anion exchange between HCrO 4 -and SO 4 2-dominated the adsorption process in the present system.…”
Section: Effect Of Ph Valuescontrasting
confidence: 56%
See 1 more Smart Citation
“…Chemical oxidation yields schwertmannite with a specific surface area of 4–14 m 2 ·g − 1 [ 30 ], 2.06–16.3 m 2 ·g − 1 [ 44 ], 48.2 m 2 ·g − 1 [ 27 ], and even 130.9 m 2 ·g − 1 [ 45 ]. In contrast, rapid hydrolysis enables the synthesis of schwertmannite with a specific surface area several times greater, e.g., 165 m 2 ·g − 1 [ 46 ], 199.4 m 2 ·g − 1 [ 47 ], 206.1 m 2 ·g − 1 [ 29 ], and even 325.5 m 2 ·g − 1 [ 48 ]. The density of SCH A and SCH B was determined using a pycnometer, and amounts to 3.54 and 3.75 g·cm − 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The pI value order (called pH zpc in most reported references) is as follows: 7.2 (AMD) 45 > 5.4 (bio-ferrooxidation) 59 > 5.1 (chem. oxidation) 34 > 4.2 (fast hydrolysis) 60 > 3.7 (fast hydrolysis) 61 > 3.05 (fast hydrolysis). 62 According to the above order, natural Sch may have a higher pH zpc value, and Sch obtained using fast hydrolysis may have the lowest pH zpc value.…”
Section: Synthetic Strategy – Structural Characteristicsmentioning
confidence: 99%